Observations with fast visible cameras in high power Deuterium plasma experiments in the JET ITER-like wall tokamak. (December 2020) - Losada, U.; Manzanares, A.; Balboa, I.; Silburn, S.; Karhunen, J.; Carvalho, Pedro J.; Huber, A.; Huber, V.; Solano, Emilia R.; de la Cal, E.
Highlights: A system of IR and visible cameras allows the monitoring of the wall and Divertor surface temperatures as well as the study of plasma dynamics and spectroscopic properties in JET ITER-like plasmas. Two high speed visible cameras allow the proper observation of differnt plasma phenomena and a large fraction of the vacuum vessel Two high speed visible cameras allow the observation of a large fraction of the vacuum vessel. The radial propagation velocity of Edge Localized Modes can be explored with fast cameras working at 20, 000 images per second and with exposure times of 50 usec. Shattered Injected Pellets (SPI) are injected into the plasma to mitigate disruptions. Abstract: High speed visible imaging allows to visualize the 2-dimensional dynamics of fast phenomena in the boundary layer of fusion plasmas. Here we describe the two high speed visible cameras currently operating in the JET tokamak, enabling the simultaneous observation of a large fraction of the JET tokamak vacuum vessel with the appropriate configuration for many different plasma phenomena. As an example we discuss recent observations on the spatial and temporal dynamics of visible emission at the outer wall during Edge Localized Modes (ELMs) and the penetration of Shattered Injected Pellet (SPI) into the plasma.